1963
DOI: 10.1039/tf9635901163
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of methane at about 400°C. Part 1.—Reaction catalyzed by the photodecomposition of acetone

Abstract: The reaction of methane and oxygen at about 400°C catalyzed by the photodecomposition of acetone has been studied using a static system. With a new vessel at 414°C the thermal reaction was negligible and the maximum rate of pressure change Lax) was proportional to and independent of the intensity of the ultra-violet radiation. The products were carbon monoxide, carbon dioxide, water, formaldehyde and methanol, the concentration of the last two rising to a maximum and the alcohol not being formed until after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…formaldehyde, it probably comes directly from the breakdown of the acetonyl peroxy radical Exam ination of a scale molecular model shows th a t this reaction involves rela tively little movement of the oxygen atom, which has to be followed only by the necessary electron redistribution to allow the products to separate. This is a certain am ount of supporting evidence for this reaction which has also been proposed by Hoare & Wellington (i960) and by Fisher & Tipper (1963 a). Thus, Wenger & K utschke (1959) have suggested a formally similar reaction to explain their results on the oxidation of azomethane CH3.N :N .C H 3 + 0 2 = CH3 + N 20 + H C H 0 and Dunn & K utschke (1958) have shown by tracer studies th a t about 90% of the carbon dioxide formed in the photoxidation of acetone a t 120 to 175 °C came from the central carbon atom.…”
Section: I 255supporting
confidence: 85%
See 1 more Smart Citation
“…formaldehyde, it probably comes directly from the breakdown of the acetonyl peroxy radical Exam ination of a scale molecular model shows th a t this reaction involves rela tively little movement of the oxygen atom, which has to be followed only by the necessary electron redistribution to allow the products to separate. This is a certain am ount of supporting evidence for this reaction which has also been proposed by Hoare & Wellington (i960) and by Fisher & Tipper (1963 a). Thus, Wenger & K utschke (1959) have suggested a formally similar reaction to explain their results on the oxidation of azomethane CH3.N :N .C H 3 + 0 2 = CH3 + N 20 + H C H 0 and Dunn & K utschke (1958) have shown by tracer studies th a t about 90% of the carbon dioxide formed in the photoxidation of acetone a t 120 to 175 °C came from the central carbon atom.…”
Section: I 255supporting
confidence: 85%
“…We may, however, estimate the lifetime of the hydroperoxide a t 284 °C to be interm ediate between th a t of ethyl hydroperoxide (about 15 s) and hydrogen peroxide (5*6 x 106 s). The only other information upon which an estimate may be based are the experiments by Fisher & Tipper (19636) which lead to the half-life of methyl hydroperoxide being ~ 30 s at 395 °C; assuming the activation energy for the homogeneous decomposition is the same as for other organic hydroperoxides, namely 38 kcal, this leads to a life-time of about 104 s a t 284 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Similar relationships were observed in ref. 20, and it was concluded that the detected organic peroxide is methylhydroperoxide, which is formed according to the following reactions:…”
Section: Comparison Of Figures 2 Andmentioning
confidence: 99%
“…In ref. 20 it was mentioned that when the surface was "nonactive" peroxides were not observed and the rate of the reaction was lower than that found in reactors having an "active" surfacewhich obtains when the reaction is photoinitiated. On "active" surface hydrogen peroxide, methyl hydroperoxide and methanol were formed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation